Pengendalian Kualitas Produksi Kain Twill Maxfill Dengan Menggunakan SPC Dan FMEA Dibagian Inspecting PT. Sipatex - Elsa Nurhalifah; Ujang Cahyadi; Dedi Sa'dudi Taptajani (Jurnal Kalibrasi, 2026)
PT Sipatex Putri Lestari is a textile manufacturing company that produces greige fabric through processes including texturizing, sizing, dyeing, printing, coating, and yarn dyeing. The defect rate in the production process, particularly the weft missing defect, still exceeds the predetermined tolerance limits, making quality control necessary. This study aims to analyze the causes of fabric defects, identify the factors contributing to defects, and determine ways to reduce defects in the fabric production process. In addition, this research seeks to identify quality improvement measures to minimize defect levels in the production of twill maxfill fabric. This study employs Statistical Process Control (SPC) and Failure Mode and Effect Analysis (FMEA) methods. The results show that the most dominant defect is the weft missing defect, accounting for 42% of total defects. Furthermore, several factors causing defects were identified using fishbone diagram analysis, including human factors, machine factors, material factors, and method factors. Subsequently, FMEA analysis was conducted to determine priority scales based on the Risk Priority Number (RPN) values. Based on the highest RPN value, it was found that malfunctioning or damaged machine fillers were the main cause of defects. Therefore, the proposed corrective actions include servicing or replacing the machine fillers to ensure that damaged or dirty fillers can be promptly addressed. This is intended to ensure that the resulting products meet high quality standards and to minimize defects during the production stage. In addition, routine and continuous machine cleaning and maintenance, as well as inspections of machine readiness prior to operation, are considered essential. After implementing the proposed improvements for five days, the results indicate that the corrective actions successfully helped minimize defects by repairing the damaged fillers.